Facile Preparation of Aryl Nitriles from Aryl Aldehydes in PEG-DME 250 - Kang, Solbe; Lee, Jong C. (Letters in Organic Chemistry, 2022)
A facile and efficient method is reported for the one-pot transformation of aryl aldehydes to aryl nitriles using hydroxylamine hydrochloride and phosphorus tribromide in PEGDME 250. The conversion of various aryl aldehydes to the corresponding aryl nitriles occurred smoothly in high yields under the present reaction conditions.
Keywords: nitriles